Changes in serum lipids in patients with rheumatoid arthritis treated with a combination of tocilizumab and methotrexate compared with methotrexate alone for 24 weeks of observation - E. V. Udachkina; D. S. Novikova; T. V. Popkova; E. Yu. Panasyuk; A. S. Avdeeva; A. V. Volkov; I. G. Kirillova; E. I. Markelova; E. N. Aleksandrova; A. A. Novikov; E. L. Nasonov (Рациональная фармакотерапия в кардиологии)
Background. According to the some studies tocilizumab therapy (TCZ) in patients with rheumatoid arthritis (RA) is accompanied by deterioration of blood lipid profile. Aim. To study changes in serum lipid parameters in patients with RA treated with a combination of tocilizumab and methotrexate compared with methotrexate alone for 24 weeks of observation. Material and methods. Patients (n=72) with RA were included into the pilot non-randomized 24-week study and divided in two groups: 1) TCZ+MTX group (n=39; women 30; median age 51 [43-55] years; 6 i.v. infusions of TCZ 8 mg/kg + МТX 10-20 mg/week); 2) MTX group (n=33; women 23; mеdian age 56 [48-63] years; MTX 7.5-20 mg/week). Results. At the baseline, similar proatherogenic blood profile was observed in both groups. The patients of MTX group more frequently took statins (n=19; 57.6%) compared with the group TCZ+MTX (n=7; 18%), (p<0.05). The lipid levels correlated positively with traditional risk factors (p<0.05). RA activity and duration correlated negatively with high density lipoprotein cholesterol (HDL-C), (p<0.05). Good/satisfactory anti-inflammatory effect was achieved in both groups after 24 weeks of treatment. Patients of TCZ+MTX group showed an increase in total cholesterol and HDL-C levels by 11% and 110%, respectively and decrease in plasma atherogenic index (PAI) by 47%, (p<0.05). HDL-C level increased by 22% and PAI decreased by 16% in patients of MTX group (p<0.05). Among patients of MTX group without statin therapy HDL-C as well as non-HDL-C levels were increased by 24% and 27%, respectively (p<0.05); PAI did not change significantly in this subgroup. Among patients of MTX group treated with statins isolated increase in HDL-C level by 22% and decrease in PAI by 37.3% (p<0.05) were observed. A number of patients with achieved target levels of all studied lipid parameters did not change significantly in both groups. Conclusions. TCZ+MTX combined therapy as well as MTX monotherapy are associated with similar improvement in lipid parameters. Adjusted statin doses may be needed to achieve target serum lipid profile in RA patients.